Neurodevelopmental and functional outcome in hypoplastic left heart syndrome after Hybrid procedure as stage I - Knirsch, Walter; De Silvestro, Alexandra; von Rhein, Michael (Frontiers in Pediatrics, 2023)
Background: Patients with Hypoplastic Left Heart Syndrome (HLHS) undergoing staged palliation until Fontan procedure are at risk for impaired neurodevelopmental (ND) outcome. The Hybrid procedure with bilateral pulmonary artery banding, ductal stenting, and balloon atrioseptostomy may offer a less invasive stage I procedure compared to the Norwood stage I procedure avoiding early neonatal cardiopulmonary bypass (CPB) surgery. Despite altered fetal cerebral hemodynamics, the type of stage I procedure may be a covariate influencing ND outcome and functional outcome may also be altered due to postponing neonatal CPB surgery. Within this review we analyzed ND outcome as well as functional outcome after Hybrid procedure as stage I procedure. Methods: The review analyzed original publications (OP) published before March 15, 2022 identified by Cochrane, EMBASE, OVID, Scopus, and Web of science. An OP was included if short-to-long-term neurodevelopment outcome, brain development, somatic, and cardiac outcome in patients for HLHS and variants treated by Hybrid procedure was analyzed. In addition to database searches, we reviewed all references of the analyzed OP to obtain a comprehensive list of available studies. Author, year of publication, demographic characteristics of study population, study design (prospective or retrospective), study assessment and main findings were summarized. Results: Twenty-one OP were included with data of patients with ND outcome and functional cardiac outcome. Overall, there is an impaired mid-term ND outcome in patients with Hybrid procedure as stage I for HLHS. Only slight differences between stage I procedures (Hybrid vs. Norwood) in two comparing studies have been determined affecting right ventricular remodeling, short- and mid-term ND outcome, reduced brain growth until two years of age, sufficient quality of life, altered hemodynamics influencing brain volumes and cerebral perfusion pattern. Conclusions: Despite some minor differences regarding the mid-term follow up in patients with HLHS comparing Hybrid vs. Norwood procedure, its impact on ND outcome seems rather low. This may be explained by the large number of covariates as well as the small study populations and the different selection criteria for patients undergoing Hybrid or Norwood procedure as stage I.